Consciência política e participação cidadã de estudantes de administração de uma universidade pública federal no sudeste do Brasil - Martins, Geruza Ferreira (2014)
In a setting where public participatory spaces are broadened in Brazil, one has to consider the expectations about raising socio-political values among university students in their process of professional and citizen qualification, in face of criticism to